SURFACE WATER MODELLING AT LAMONG BAY - Cahya Buana; Her Widyastuti; Wahju Herijanto; Catur Arif Prastyanto; Anak Agung Gde Kartika; Budi Rahardjo; Istiar Istiar (Journal of Civil Engineering, 2009)
Development of ports in the Lamong Bay may result in changes in flow pattern and velocity. In order for such development does not cause a big impact analysis should be made based on the understanding of the physical processes that will occur. This study examined the flow pattern and velocity of Lamong Bay. Existing model simulation results indicate that the direction of motion of the water flow to the front line of Gresik Ports were more integrated with the dominant direction were Northwest - Southeast, whereas in front of the Port of Tanjung Perak flow direction were dominated by West - East. The findings also suggest the direction of movement of currents in the Lamong Bay were more spread and dominated by the movement parallel to the contour of the coastline.